1997
DOI: 10.1111/j.1469-7610.1997.tb01597.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication between Parents and Deaf Children: Implications for Social‐emotional Development

Abstract: Parent-child communication plays a central role in social growth, as it does in other domains of development. Over 90% of deaf children, however, have hearing parents who frequently do not have a fully effective means of communicating with them. This paper examines the role of effective parent-child communication in the social and emotional development of deaf children. Evidence concerning relations between early communication and social-emotional development of deaf children is reviewed, and superficial diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(123 citation statements)
references
References 40 publications
2
117
0
4
Order By: Relevance
“…The finding that our deaf participants' answers equaled the answers of their hearing peers in number of arguments is probably also a direct consequence of this procedure. Others have also argued that the interactions of deaf children with their hearing parents tend to be short and simple Vaccari & Marschark, 1997). Now that the children in our experiment were able to communicate with a skilled interpreter, however, they proved to be just as elaborate as the hearing group.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The finding that our deaf participants' answers equaled the answers of their hearing peers in number of arguments is probably also a direct consequence of this procedure. Others have also argued that the interactions of deaf children with their hearing parents tend to be short and simple Vaccari & Marschark, 1997). Now that the children in our experiment were able to communicate with a skilled interpreter, however, they proved to be just as elaborate as the hearing group.…”
Section: Discussionmentioning
confidence: 82%
“…The communication skills of hearing parents to their deaf offspring seldom exceed the level of a four-year-old. This results in short and simple interactions, in which the interlocutors openly display their impatience with one another and show reluctance to talk about abstract concepts, such as emotions and beliefs (Vaccari & Marschark, 1997). However, other studies have shown that interactions between hearing teachers-who learned either sign language or signsupported English-and deaf pupils are also limited.…”
mentioning
confidence: 99%
“…Impoverished emotional coaching has been found to be associated with less positive peer relationships (Hart, Ladd, & Burleson, 1990). Deaf children are unlikely to receive little emotional coaching within the family setting: Most deaf children (90%) have hearing parents whose sign language skills usually do not exceed those of a four-year-old, and it is known that these parents talk less about mental phenomena, such as emotions and their underlying causes, with their deaf children (Vaccari & Marschark, 1997). Unlike their hearing peers, deaf children also cannot profit from hearing other people's conversations and must rely more on autodidactic methods for their emotion socialization.…”
Section: Discussionmentioning
confidence: 99%
“…Over 90% of congenitally deaf children are born to hearing parents (Vaccari and Marschark 1997;Moores 2001), which implies that most families are unfamiliar with the issue. But also among parents with earlier experiences in deafness information and knowledge plays a role Á both enabling and confining.…”
Section: Information and Knowledgementioning
confidence: 99%
“…It is true that empirical research shows that the influence of the medical model on parents' care-related experiences and decision-making is strong (e.g. Kluwin and Stewart 2000), which is hardly surprising given that over 90% of congenitally deaf children are born to hearing parents, who Á as opposed to deaf parents Á have no experience of deafness or Deaf identity (Vaccari and Marschark 1997). But should we conclude that the distinction between medical and social/cultural-linguistic models aligns perfectly with the dividing line between hearing and deaf parents?…”
Section: Introductionmentioning
confidence: 99%